DISTRIBUTION, GROWTH AND REGENERATION OF LARIX GMELINII (RUPR.) RUPR. ALONG THE TIMBERLINE ECOTONE OF MT. DAL'NYAYA PLOSKAYA, CENTRAL KAMCHATKA (18th Symposium on Polar Biology) - オキツ, ススム; OKITSU, Susumu (National Institute of Polar Research, 1997)
P(論文) Variation in size structure and annual height growth of a Larix gmelinii (RUPR.) RUPR. population was documented along a timberline ecotone from the closed forest margin (910 m altitude) up to the last trees of L. gmelinii (960 m altitude) on the western slope of Mt. Dal'nyaya Ploskaya, central Kamchatka. The maximum height and total basal area of L. gmelinii trees decreased gradually along the timberline ecotone. The stretch of this timberline ecotone reached to ca. 300 m in distance, being shorter than that of Mt. Paektu, North Korea. No apparent wind-shaped trees occur along the timberline ecotone even at the uppermost part of it. It might be concluded, from the previous two points, that the most important factor promoting this timberline ecotone is a shortage of summer heat. Tree height distribution of a stand of L. gmelinii generally shows higher a number of taller trees with a smaller number of shorter trees, suggesting discontinuous regeneration of L. gmelinii. The wide variety of annual height growth of L. gmelinii within a stand supports discontinuous regeneration. The population of the upper part of the timberline ecotone maintains its regeneration mainly by layering of branches. departmental bulletin paper